2016
DOI: 10.1121/1.4950206
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency ultrasound for the delivery of therapeutics to the gastrointestinal tract

Abstract: Rapid and effective drug delivery to the gastrointestinal (GI) tract can be a significant challenge. This is because of the harsh environment present in the GI tract and fast transit times in disease states. Physical enhancers, such as ultrasound (US), may enable the rapid delivery of therapeutics while circumventing the need for formulation development. Despite being investigated for other uses, low frequency US has not been studied for GI-based delivery previously. Our group has developed a hand-held device … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For example, a more than 20-fold enhancement of drug permeation compared to a conventional enema has been achieved by applying a 1-minute treatment of low-frequency ultrasound generated by a rectal probe in Yorkshire pigs. [259] Similar enhancement can be achieved for the delivery of hydrocortisone and mesalamine. [136] …”
Section: Breaching Biological Barriers Other Than Skinmentioning
confidence: 99%
“…For example, a more than 20-fold enhancement of drug permeation compared to a conventional enema has been achieved by applying a 1-minute treatment of low-frequency ultrasound generated by a rectal probe in Yorkshire pigs. [259] Similar enhancement can be achieved for the delivery of hydrocortisone and mesalamine. [136] …”
Section: Breaching Biological Barriers Other Than Skinmentioning
confidence: 99%
“…This approach employs a low frequency ultrasound to trigger drug delivery at lower GIT via causing transient cavitation, which produce microjets to enhance drug permeation through gastrointestinal mucosa [46]. Schoellhammer et al [47] reported the development a hand-held device, which use a low frequency ultrasound, as a reversible and painless method to enhance mesalamine delivery in the treatment of ulcerative colitis and Crohn' disease. This device was coadministered superficially into the rectum of Yorkshire pigs with a mesalamine enema.…”
Section: Ultrasound Mediated Approachmentioning
confidence: 99%